2006
DOI: 10.2337/db06-0788
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Analysis of Insulin Gene Promoters

Abstract: DNA sequences that regulate expression of the insulin gene are located within a region spanning ϳ400 bp that flank the transcription start site. This region, the insulin promoter, contains a number of cis-acting elements that bind transcription factors, some of which are expressed only in the ␤-cell and a few other endocrine or neural cell types, while others have a widespread tissue distribution. The sequencing of the genome of a number of species has allowed us to examine the manner in which the insulin prom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
139
1
1

Year Published

2007
2007
2020
2020

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 159 publications
(143 citation statements)
references
References 144 publications
2
139
1
1
Order By: Relevance
“…The occurrence of this short-range DNA loop is consistent with the observation that only ϳ300 bp of the gene upstream of the promoter are sufficient to confer high-level, cell-specific activity of the promoter in both cellbased systems and transgenic animals (13). We show here using a novel application of the 3C technique in vitro that two EcoRI sites located at Ϫ623 and ϩ761 bp (relative to the transcriptional start site) are brought into close proximity of one another such that ligation of these EcoRI sites is statistically enhanced by the presence of Pdx1, NeuroD1, and E47.…”
Section: Discussionsupporting
confidence: 59%
See 1 more Smart Citation
“…The occurrence of this short-range DNA loop is consistent with the observation that only ϳ300 bp of the gene upstream of the promoter are sufficient to confer high-level, cell-specific activity of the promoter in both cellbased systems and transgenic animals (13). We show here using a novel application of the 3C technique in vitro that two EcoRI sites located at Ϫ623 and ϩ761 bp (relative to the transcriptional start site) are brought into close proximity of one another such that ligation of these EcoRI sites is statistically enhanced by the presence of Pdx1, NeuroD1, and E47.…”
Section: Discussionsupporting
confidence: 59%
“…Based on DNA binding studies in vitro and reporter gene analysis in transfected mammalian cells, Pdx1 is believed to bind to the A-boxes and NeuroD1 to the E-boxes (11,12). Importantly, in the rodent and human Ins genes, tandemly occurring E/Aboxes (referred to as the "E2/A3" and "E1/A1" elements) are situated within a crucial 350-bp regulatory region upstream of the transcriptional start site (13). In reporter gene assays, these tandem elements synergistically activate gene transcription response to Pdx1 and NeuroD1 overexpression (12,14).…”
mentioning
confidence: 99%
“…Insulin, a pancreatic peptide hormone is regulated by glucose at various steps of insulin gene expression such as transcription, splicing, mRNA stability and translation [1][2][3][4]. The increase in insulin production within an hour of the glucose treatment occurs primarily due to increase in translation with no significant enhancement in mRNA levels [5].…”
Section: Introductionmentioning
confidence: 99%
“…Comparative sequence analysis has revealed that the overall homology of the insulin promoter (-600 to +1 region) between humans and rodents is only ~45-48%. Many features of the cis-regulatory elements, such as the cyclic AMP response element, negative regulatory element, and CCAAT box, also display marked species specificity (Hay and Docherty, 2006;Boam et al, 1990). The exact and relative contributions of the two insulin genes to rodent glucose regulation remain unclear and often overlooked, thereby limiting data extrapolation to the single insulin gene system in humans.…”
Section: Fig 2: Species-specificity Of Glucose Regulationmentioning
confidence: 99%